The Influence Of Product Quality And Trust On Customer Satisfaction At Intan Workshop, Kota Raya Lahat - Wahyu Fajri; Melia Andayani; Saparudin Saparudin (Journal of Management, Economic, and Accounting, 2026)
This research aims to determine how Product Quality and Trust affect Customer Satisfaction at the Intan Workshop in Kota Raya Lahat both partially and simultaneously. The sample in this study consists of 40 respondents. The sampling method used by the researcher is Incidental sampling. This type of research is quantitative, using multiple linear regression analysis techniques processed with SPSS, resulting in the regression equation Y=3.076+0.779X1+0.139X2. The results of this study indicate: there is a significant effect of Product Quality on Customer Satisfaction at the Intan Workshop in Kota Raya Lahat, and there is a significant effect of Trust on Customer Satisfaction at the Intan Workshop in Kota Raya Lahat. The F test shows that Product Quality and Trust simultaneously affect Customer Satisfaction at the Intan Workshop in Kota Raya Lahat.